Design of Chili Paste Logo to Promote Image Products in the Community of Nayom Subdistrict Phetchabun Province - Peerachaakkarachai, Kankulnat; Kanya, Rungthip (Rajamangala University of Technology Tawan-ok Social Science Journal, 2025)
The purposes of this research were to 1) design and develop a chili paste logo to promote the image of products in the community of Nayom Subdistrict Phetchabun Province and 2) study consumers satisfaction toward the chili paste logo designed to promote the image of products in the community of Nayom Subdistrict Phetchabun Province. Through interviewed with key informants including community leaders and community representatives from 15 villages of 45 persons selected through quota sampling and a sample group used in the study was a questionnaire with consumers of 100 persons selected through convenience sampling. Data were collected using interview forms and questionnaires. The statistics used in the data analysis included percentage, mean and standard deviation. The research results were found as follows: 1) design and development of the chili paste logo to promote the image of products in the community of Nayom Subdistrict Phetchabun Province. By studying the problems and needs, it was found that there was no chili paste logo that could indicate the community’s identity, and there was also a lack of knowledge in product logo design. Consequently, the community’s products lacked recognition among consumers. During the design and development process of the logo, the community was engaged to express their opinions, provide advice, and utilize colors, symbols, fonts, and images that conveyed the meaning of the product. Experts assessed the quality of the logo at a higher level (𝑥̅ = 4.34, S.D. = 0.48), indicating that the logo design can create recognition among consumers and onlookers. And 2) study on consumer satisfaction towards the chili paste logo designed to promote the image of products in the community of Nayom Subdistrict Phetchabun Province. The results found that overall satisfaction was at a high level (𝑥̅ = 4.32, S.D. = 0.59).